Characterisation of the lytic viral peptide LysM and its target, the bacterial Lipid II flippase MurJ - Bannon, SD (2024)
Cell wall synthesis is a highly conserved and essential process in bacteria. The cell wall precursor, Lipid II, is transported across the plasma membrane by the flippase MurJ, a newly discovered putative antibiotic target that is non-redundant in many species. While the mechanism of flipping Lipid II was elucidated following a series of structures published during the proceedings of this DPhil project, there are still open questions about the mechanism employed by MurJ. Importantly, there are no available structures of Gram-positive MurJ, which have structural differences to their Gram-negative counterparts. The Escherichia coli-infecting levivirus, enterobacteria phage M, targets MurJ using a 37-amino acid peptide, LysM. The molecular mechanism of this natural example of MurJ inhibition has yet to be understood, and there is a need to evaluate the potential of viral inhibitors from the perspective of antibiotic discovery. This thesis combines in silico, in vivo, and in vitro experiments for the characterisation of LysM, determining that it is a helical peptide that spans the membrane with an amphipathic C-terminal helix that lies on the membrane surface. A helical kink occurs at the essential residue D18, orienting the C-terminal and N-terminal helices near-perpendicular to each other, with the N-terminal helix pointing straight down into the membrane. One face of the peptide confers lytic activity through a concerted contribution of polar and hydrophobic residues, which reveals a putative binding face between LysM and MurJ. A purification strategy for LysM was also established that provides a platform for future binding and structural studies, and constructs were made for confirming the N-in topology and for the co-expression of LysM and MurJ. B. subtilis MurJ was purified in multiple conditions and structurally screened. However, stability and binding studies suggested that this protein was unsuitable for further study. Homologues were screened, along with the novel flippase Amj, identifying suitable constructs for future purification and structural studies. These experiments and constructs allow for a wealth of future characterisation and establish a direct pathway for co-purification of the putative complex for Cryo-EM.